Zu Fragen der biologischen Methode der Schädlingsbekämpfung in der Sowjetunion (Eindrücke einer Studienreise). - Fankhänel, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1963)
There are reported some problems of biological control in the Soviet Union and its organization with special reference to theoretic investigations and practical application of high specialized, oligophageous and polyphageous predators and parasites as like as microbiological control methods.